2020
DOI: 10.3201/eid2605.191414
|View full text |Cite
|
Sign up to set email alerts
|

Crimean-Congo Hemorrhagic Fever Virus Endemicity in United Arab Emirates, 2019

Abstract: We conducted a cross-sectional survey of Crimean-Congo hemorrhagic fever virus (CCHFV) in dromedary camels and attached ticks at 3 locations in the United Arab Emirates. Results revealed a high prevalence of CCHFV-reactive antibodies in camels and viral RNA in ticks and camel serum, suggesting the virus is endemic in this country.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 8 publications
(12 reference statements)
3
44
0
Order By: Relevance
“…While this paper was in preparation, partial CCHFV S-and M-segment sequences from H. dromedarii ticks and camels from the UAE were published separately. In addition to molecular detection, this study reported that 67 % of sampled camels had CCHFV antibodies, which further supports the view that camels in the region are commonly infected with CCHFV [8]. The partial sequences obtained by Camp et al are almost identical to our current full-length sequences, which also have high sequence identity to previous partial sequences reported from camel ticks in Egypt [20], suggesting that virus strains belonging to the Asia 4 lineage might not only be prevalent in camels and camel ticks in the UAE .…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…While this paper was in preparation, partial CCHFV S-and M-segment sequences from H. dromedarii ticks and camels from the UAE were published separately. In addition to molecular detection, this study reported that 67 % of sampled camels had CCHFV antibodies, which further supports the view that camels in the region are commonly infected with CCHFV [8]. The partial sequences obtained by Camp et al are almost identical to our current full-length sequences, which also have high sequence identity to previous partial sequences reported from camel ticks in Egypt [20], suggesting that virus strains belonging to the Asia 4 lineage might not only be prevalent in camels and camel ticks in the UAE .…”
Section: Resultssupporting
confidence: 81%
“…While this paper was in preparation, partial CCHFV S- and M-segment sequences from H. dromedarii ticks and camels from the UAE were published separately. In addition to molecular detection, this study reported that 67 % of sampled camels had CCHFV antibodies, which further supports the view that camels in the region are commonly infected with CCHFV [8]. The partial sequences obtained by Camp et al .…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…To our knowledge, camels were never screened for CCHFV-specific antibodies in Mauritania before. Only a limited number of CCHFV seroprevalence studies in camels have been carried out so far [28], with recent findings indicating prevalences of 5.3% in Iran [29], 10.5-14.4% in Niger [30], 21.3% in Sudan [31] and 67% in the United Arab Emirates [32] respectively. Using the newly established camel-specific ELISA, this study revealed a surprisingly high proportion of positive animals (81%).…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…Hyalomma asiaticum has been confirmed to be the main vector of CCHFV in Xinjiang, China (Guo et al, 2017; Moming et al, 2018). Hyalomma dromedarii , as a tick species mainly parasitic to camels, has also been demonstrated to carry CCHFV and infect the host (Camp et al, 2020; Moshaverinia and Moghaddas 2015). Strangely enough, H. dromedarii was found in both Left and Right Banner, while CCHFV was detected only in H. dromedarii of females from Alxa Right Banner.…”
Section: Discussionmentioning
confidence: 99%